PELATIHAN DAN PENDAMPINGAN ANALISIS KREDIT BAGI LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT TEGALLINGGAH, KABUPATEN GIANYAR, BALI - Ni Nyoman Reni Suasih; Ida Ayu Nyoman Saskara; Ni Putu Wiwin Setyari; Putu Ayu Pramitha Purwanti; I Made Endra Kartika Yudha (Universitas Mataram, 2022)
The Village Credit Institution (LPD) is a traditional-based financial institution that has proven to be an important element in the economy of rural communities in Bali. During the last two decades, LPDs in various traditional villages have shown good development, but in some traditional villages there are still many LPDs that have not developed as expected, one of which is characterized by an unhealthy status or high NPL. One of them is the Tegallinggah Traditional Village LPD which is located in Bedulu Village, Blahbatuh District, Gianyar Regency. The purpose of this community service activity is to provide training and assistance in credit analysis for the Tegallinggah Traditional Village LPD. The method used is through lectures, discussions, training, and mentoring. The result of this activity is the increasing understanding of the Tegallinggah Traditional Village LPD managers regarding credit analysis. In addition, the Tegallinggah LPD manager has also been able to carry out credit analysis more carefully and in accordance with applicable standards. This community service activity has been carried out to provide education and training on credit analysis so that it is expected to reduce the NPL of the Tegallinggah Traditional Village LPD. After the implementation of activities related to efforts to reduce NPL, it is necessary to carry out activities to improve LPD performance. These activities include the dissemination of various services that can be provided by LPD, including education on the use of benefits, so that the benefits can be felt on the local community's economy.